Faecal metaproteomics analysis reveals a high cardiovascular risk profile across healthy individuals and heart failure patients - Chaoran Yang; Leticia Camargo Tavares; Han-Chung Lee; Joel R. Steele; Rosilene V. Ribeiro; Anna L. Beale; Stephanie Yiallourou; Melinda J. Carrington; David M. Kaye; Geoffrey A. Head; Ralf B. Schittenhelm; Francine Z. Marques (Gut Microbes)
The gut microbiota is a crucial link between diet and cardiovascular disease (CVD). Using fecal metaproteomics, a method that concurrently captures human gut and microbiome proteins, we determined the crosstalk between gut microbiome, diet, gut health, and CVD. Traditional CVD risk factors (age, BMI, sex, blood pressure) explained < 10% of the proteome variance. However, unsupervised human protein-based clustering analysis revealed two distinct CVD risk clusters (low-risk and high-risk) with different blood pressure (by 9 mmHg) and sex-dependent dietary potassium and fiber intake. In the human proteome, the low-risk group had lower angiotensin-converting enzymes, inflammatory proteins associated with neutrophil extracellular trap formation and auto-immune diseases. In the microbial proteome, the low-risk group had higher expression of phosphate acetyltransferase that produces SCFAs, particularly in fiber-fermenting bacteria. This model identified severity across phenotypes in heart failure patients and long-term risk of cardiovascular events in a large population-based cohort. These findings underscore multifactorial gut-to-host mechanisms that may underlie risk factors for CVD.